The legal nature of the public administrator’s management contract in Romania. Aspects of comparative law - Maria-Luiza Hrestic; Ivan Vasile Ivanoff (Juridical Tribune, 2022)
Public administrator is a new function, which was introduced into the Romanian legislation by the Law no. 286/2006 amending and supplementing Law no. 215/2001; the management contract, under which public administrators carry out their responsibilities, is not defined either by legislation or by doctrine, because there are various opinions in the specialty literature ranging from its qualification as a labour contract to the civil nature of this legal relationship. In this article, we try to provide a basis for the administrative contract view about the management contract concluded between a public administrator and the public executive authority within an administrative territorial unit.